Stressors and Coping Strategies among Adolescents Studying Public Schools in Kathmandu - Gautam, Prakash Kumar; Paudel, Kamala (Nepal Journal of Multidisciplinary Research, 2025)
Background: Adolescence is a pivotal phase marked by physical, emotional, and psychological changes, often accompanied by stress from academic, social, and family pressures. Globally, 20% of adolescents face mental health issues, with depression and anxiety being common. In Nepal, stressors like socioeconomic disparities and limited mental health resources further compound challenges. Methodology: Using a cross-sectional design, this study explores stress levels and coping strategies among 239 adolescents in government schools in Tokha Municipality, Kathmandu. Data were collected via the Perceived Stress Scale (PSS-10) and Brief Cope Inventory, analyzed using descriptive and inferential statistics, and gender differences examined. Results: Results show 84% of adolescents experienced moderate stress, with females reporting higher levels than males. Stress stemmed more from regret and unmet expectations than nervousness. Problem-focused strategies like planning and active coping were most common, alongside emotion-focused approaches such as emotional support and acceptance. Avoidant coping was less frequent, though more prevalent among females. Humor was rarely used. While stress levels varied by gender, both employed similar adaptive coping methods. Conclusion: The study highlights the need for targeted interventions, especially for females, to promote adaptive strategies like problem-solving and emotional support. Incorporating humor into stress management programs could also be beneficial. By fostering resilience and reducing avoidant coping, educators and policymakers can better support adolescent mental health. Novelty: This research offers valuable insights into stress and coping in low-resource settings, guiding culturally relevant interventions in Nepal and similar contexts.